2020
DOI: 10.26630/jk.v11i2.2134
|View full text |Cite
|
Sign up to set email alerts
|

Kelelahan Kerja pada Pekerja di PT. Indonesia Power Unit Pembangkitan dan Jasa Pembangkitan (UPJP) Priok

Abstract: Work fatigue is an important problem that needs to be resolved because can cause work accidents and can have an impact on workers' health. Based on the result of interviews in early 2020, there was one worker who was unconscious due to work fatigue where a similar case had never happened before in the last 5 years. Workers complain of feeling dizzy, tired all over, fever, frequent drowsiness, trembling, feeling heavy in the head, and feeling thirsty while working. The purpose of this study was to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
1
2
0
12
Order By: Relevance
“…8 This study is not in line with Safira (2020) which states that there is a relationship between nutritional status with fatigue on workers occupational status of nutrition is not normal at risk 5 times more likely to experience fatigue work, while according to the research Anwar, et al (2018) and research Suryaningtyas (2017) concluded that there is no relationship between nutritional status with work fatigue in workers. 9 Nutritional Status has a positive influence on the increase of working capacity if calories workers are not in accordance with the needs of his body then perceived by the workers is the fatigue which causes the movement of the body becomes slow.…”
Section: Discussionmentioning
confidence: 99%
“…8 This study is not in line with Safira (2020) which states that there is a relationship between nutritional status with fatigue on workers occupational status of nutrition is not normal at risk 5 times more likely to experience fatigue work, while according to the research Anwar, et al (2018) and research Suryaningtyas (2017) concluded that there is no relationship between nutritional status with work fatigue in workers. 9 Nutritional Status has a positive influence on the increase of working capacity if calories workers are not in accordance with the needs of his body then perceived by the workers is the fatigue which causes the movement of the body becomes slow.…”
Section: Discussionmentioning
confidence: 99%
“…6 Berdasarkan data Ditjen pembinaan pengawasan ketenagakerjaan tahun 2012 menyatakan bahwa telah terjadi kecelakaan kerja sebanyak 847 kasus dan 36% dari total tersebut diakibatkan oleh faktor kelelahan. 7 Kelelahan (fatigue) merupakan salah satu faktor risiko yang berkontribusi besar terjadinya kecelakaan kerja di berbagai sektor industri. Dalam perspektif keilmuan Kesehatan dan Keselamatan…”
Section: Pendahuluanunclassified
“…Penelitian lain juga mengungkapkan bahwa kualitas tidur dapat berpengaruh terhadap kelelahan karena tidur adalah suatu bentuk recovery tubuh, jika pemulihan tubuh baik maka pekerja akan lebih siap untuk melakukan pekerjaannya. 7,11 Berdasarkan ketiga hasil hipotesis analisis model SEM menunjukkan bahwa masalah penelitian telah terjawab. Beban kerja yang berat akan mempengaruhi kualitas tidur seseorang yang pada akhirnya akan mengakibatkan kelelehan kerja.…”
Section: Pembahasanunclassified
“…2 Data dari Kementerian Tenaga Kerja Jepang pada tahun 2013 didapatkan bahwa 65% pekerja tersebut mengalami kelelahan kerja karena rutinitas pekerjaan, 28% mengalami kelelahan dalam segi mental dan 7% mengalami stres derajat berat dan merasa tersingkirkan dari lingkungannya. 3 Data dari Departemen Tenaga Kerja Indonesia pada tahun 2013 didapatkan setiap hari rata-rata terjadi 414 kecelakaan kerja, yang 27,8% nya disebabkan oleh kelelahan yang cukup tinggi, dan dari angka tersebut sekitar 9,5% menderita kecacatan. 4 Beberapa faktor dapat menyebabkan kelelahan kerja.…”
Section: Pendahuluanunclassified